CONCEPTUAL ANALYSIS OF CULTURE IN NEGATION OF THE NOTION OF POPULAR CULTURE - Nwode, Goodluck Chigbo; Danjuma, Christiana; Robert, Odey Simon (EBSU Journal of Social Sciences and Humanities, 2024)
The notion of popular culture polarises culture and grounds the relegation of the cultures dabbed unpopular or low. This paper makes a conceptual analysis of culture and popular culture, with a view to negating the notion of popular culture. Relying on secondary conceptual and theoretical literatures, the paper negates the notion of popular culture and proves it to be misleading, discriminating and a form of otherness. The descriptive analysis demonstrates that the notion has neither pragmatic representation nor semantic meaning signification in the concept of culture. The study concludes that the notion of popular culture is an elitist subjective label constructed to glorify the cultures considered popular along with their elites, while dabbing and relegating other cultures. The popular culture mentality should be corrected and subverted through sustained sensitisation, reorientation and socialisation, so as to make many realise that no culture is inferior or superior to another or the others.